Choice of law to the arbitration agreement in the absence of express choice of the parties - Fernández Rozas, José Carlos (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
There are several interrelated factors that may affect both the existence and the validity of the arbitration agreement and each of them may be subject to different laws, which may lead to divergent results and generate additional confusion. To address this problem effectively, it is crucial that arbitral tribunals and the parties involved in the arbitration pay careful attention to the distinctions between the essential and validity–related elements of the arbitration agreement, as well as to the application of the relevant law to each of them. This will help to promote consistency and certainty in the arbitral process, thereby facilitating the fair and efficientresolution of disputes. The determination of validity or not an arbitration agreement is valid under the applicable law will have a bearing on whether the dispute can be submitted to arbitration, whether court proceedings can be stayed and whether the resulting award can be set aside, or its enforcement refused. It is surprising that a mechanism such as international commercial arbitration that seeks to promote efficiencyand predictability for its users lacks a uniform response in state systems and a consensus on how to resolve the issue, creating uncertainty contrary to arbitration’s goal of achieving efficientand predictable dispute resolution. The recent contradictory practice provided by the English and French courts has again highlighted the adverse consequences for the arbitral institution of this lack of unanimity.
Keywords: International commercial arbitration; arbitration agreement; presumption of separability; existence; validity and effectiveness; applicable law; law of the seat of arbitration; principle of validation